Al-Musāhabah Al-Lughawiyah Li Kalimah Al-Hubb wa Siyaghuhā Fī Riwāyah Al-Hubb Al Maktūm Muassasatan ‘ala Al-Mudawwanah Al Lughawiyah - Syarif Husein; Moh. Ainin; Yoke Suryadarma (Department of Arabic Teaching, Faculty Tarbiyah, Universitas Darussalam Gontor, 2021)
Corpus linguistics is a well-established field of linguistic inquiry that has evolved significantly with the advancement of digital technology, particularly in the era of the Fourth Industrial Revolution (Industry 4.0). Despite its growing global application, the use of corpus linguistics in linguistic research and language education in Indonesia remains relatively limited. Various corpus analysis tools, including Sketch Engine, AntConc, WordSmith, and Lunchbox, have been developed to facilitate linguistic analysis. One important area of corpus-based research is collocation analysis, which plays a crucial role in improving language proficiency, especially vocabulary development, fluency, and speaking skills. This study aims to examine the collocations of the word al-ḥubb (“love”) in the novel Al-Ḥubb al-Maktūm using a corpus linguistics approach. A qualitative descriptive method was employed, supported by library research. The Sketch Engine platform was utilized as the primary tool for collecting and analyzing corpus data. The analysis focused on identifying the lexical forms of al-ḥubb, determining their frequency of occurrence, and examining their collocational patterns within the novel. The findings demonstrate that corpus-based analysis using Sketch Engine enables an efficient and systematic examination of lexical collocations. The approach successfully identifies the various forms and collocational patterns of al-ḥubb while simplifying and accelerating the analytical process. The study concludes that corpus linguistics has considerable potential to enhance linguistic research and Arabic language instruction in Indonesia. Therefore, broader adoption and further development of corpus-based approaches are recommended to support innovation in Arabic language teaching and learning, particularly in the areas of vocabulary acquisition and language proficiency.